Integrasi Pendidikan Karakter kedalam Pembelajaran Pendidikan Agama Islam dan Pendidikan Kewarganegaraan di Era Milenial - Hubbi, Unwanul; Ramdani, Agus; Setiadi, Dadi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
Indonesia is currently faced with the problem of weakening character. Formation of character in the nation's next generation has been pursued with various forms and efforts, but until now it has not been implemented optimally. The purpose of this study is to describe the planning, implementation, and evaluation of the strengthening of character education programs in the millennial era through the learning process of PAI (Islamic Religious Education) and Civics Education (Civics Education). This research uses a qualitative approach with descriptive methods. This research was conducted at the Islamic Middle School Khadijah Bagek Nyake East Lombok. Data collection uses observation, interviews, documentation, and questionnaires. The data analysis technique uses three activities, namely data reduction, data presentation and conclusion drawing. The results were obtained as follows: (a) Learning planning in Khadijah Bagek Nyake Aikmel Islamic Middle School is well implemented, this is evidenced by the actions taken by the teacher in compiling the syllabus, lesson plans, teaching materials and evaluation instruments before learning begins; (b) The learning process is quite good because the learning material taught is integrated with character values; (c) Evaluation of learning conducted by the teacher of student learning outcomes is optimal. While the evaluation conducted by the principal of the teacher is not optimal.